(untitled) (Global Journal of Human-Social Science, 2012)
For a very long time Nigeria scholars in various fields of endeavours have argued on the trade journalism This issue bothers on the fact that every dicks and harry dabbles into this profession either to make ends meet practice for political ambition or easily pick it up at the time of employment recession in Nigeria Journalism as a profession especially in Nigeria has been hijacked by quacks or subtly put people from other professional careers at the detriment of this noble profession In light of this the paper raised who is a professional journalist and how does non-professionalism affect the practice of journalism in Nigeria Journalists in Nigeria were used as participants while survey method was used to carry out the research Frequency distribution involving tables was used to analyse the data while the result showed that Nigeria journalists are non-professionals So relevant suggestions were recommended to help journalists develop a sense of professionalism among which are that the regulatory bodies should enforce the code of ethical conduct and rid of quacks in the profession It pushes further that proper marriage between formal education and experience along necessary training should form basis for entrance into the profession